Tinjauan Pembelajaran IPA melalui Evaluation Discrapancy Models - Yuniara Yuniara; Rita Sari; Nina Rahayu (Al - Azkiya : Jurnal Ilmiah Pendidikan MI/SD, 2021)
Learning Implementation Plan or RPP is a teaching device that must be prepared by teachers before conducting the teaching and learning process so that the results obtained can be taken into account in advance. With this preparation, it is expected that the learning process also runs systematically and in accordance with the desired stages. The purpose of this study is to validate IPA learning by using discrepancy evaluation models in MIS Paya Bujok Tunong. This research uses a type of descriptive qualitative research. The results of the study found that some planned items were not carried out, in implementation activities, the chosen approach was not all implemented, teachers also did not use learning media, and assessment only focused on aspects of knowledge only.